Association of the vertical and horizontal force-velocity profile and acceleration with change of direction ability in various sports - Baena-Raya, A.; Soriano-Maldonado, A.; Conceição, F.; Jiménez-Reyes, P.; Rodriguez-Perez, M. A. (European Journal of Sport Science, 2021)
This study aimed to assess the association of the mechanical variables derived from the force-velocity (FV) profile (i.e. theoretical maximal force [F0], velocity [V0] and maximal power output [Pmax]) with change of direction (COD) performance in soccer, basketball and tennis players. Fifty-four male athletes (soccer n = 23; tennis n = 16; basketball n = 15) were assessed for the vertical (Vrt) and horizontal (Hzt) FV profiles, COD with the dominant (D) and nondominant (ND) legs, using the modified 505 test, and sprint. Hzt FV profile parameters showed stronger associations with performance than Vrt FV profile in the three sports. Specifically, the Hzt parameter most strongly associated with COD performance was F0 in tennis (r = -0.83; p<0.001) and Pmax in soccer and basketball (r = -0.79; p<0.001). Associations between sprint times and COD test ranged from (r = 0.73-0.82) in soccer players, (r = 0.74-0.87) in tennis players and (r = 0.62-0.85) in basketball players, respectively (p<0.05). Considering the whole sample and the random effect of the type of sports, an improvement in sprint acceleration (i.e. one N/kg increase in F0 and one W/kg in Pmax) was associated with -0.15 s and -0.04 s to complete the 505 test, respectively. In conclusion, our results suggest the potential usefulness of assessing the Hzt FV profile to maximize acceleration capabilities through training interventions which, in turn, may translate into improved COD performance. However, further longitudinal and experimental research is needed to confirm this hypothesis.